The interactive nature of reality television - Heidi Penzhorn; Magriet Pitout (Communicare)
This article explores the motivating factors for viewer participation in the reality television programme, Project Fame. It looks at the interactive component of reality television, arguing that viewers are active in their media consumption. The theoretical foundation of this study is based on the uses and gratifications theory as well as the cultural studies approach to reception theory. On a methodological level, this study applies qualitative research methods in order to determine what factors motivate viewers to participate interactively in the television programme. Supported by the categories of need gratifications, this study concludes that cognitive, affective and personal integrative needs motivate viewers to utilise the various interactive opportunities and that viewers expect gratifications from participating interactively. In addition, reception theory is used to further explain viewers’ active participation and interpretation of media messages in a social and cultural context.